2020
DOI: 10.1017/s1366728920000309
|View full text |Cite
|
Sign up to set email alerts
|

Gaze and eye movement in dialogue interpreting: An eye-tracking study

Abstract: Previous studies have investigated the cognitive processes of simultaneous interpreting and translation using eye-tracking. No study has yet utilized eye-tracking to investigate cognitive load and cognitive effort in dialogue interpreting. An eye-tracking study was conducted on two groups of interpreters (experienced and inexperienced) with varying language backgrounds during a staged dialogue interpreting session. The aim of the study was to explore gaze patterns in dialogue interpreting in relation to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…For instance, based on the corpus analysis of filled pauses (e.g., uh, um) as a window into interpreters’ cognitive load, Plevoets and Defrancq (2018) found that pause frequency increased with the lexical density of the source-language texts, but was negatively associated with formulaicity of both the source-language and the target-language texts. In addition, such techniques as digital pen recording, eye-tracking and event-related potential have been applied to understand interpreters’ cognitive load (e.g., Chen, 2020; Koshkin et al, 2018; Seeber 2011; Tiselius & Sneed, 2020). For instance, a recent eye-tracking investigation by Tiselius and Sneed (2020) into dialogue interpreting, an under-examined mode of interpreting, revealed no significant difference regarding gaze patterns between experienced and inexperienced interpreters, but indicated that interpreting into L2 in a dialogue may incur more cognitive effort than interpreting into L1.…”
Section: Interpreting Ability/competence: Construct Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, based on the corpus analysis of filled pauses (e.g., uh, um) as a window into interpreters’ cognitive load, Plevoets and Defrancq (2018) found that pause frequency increased with the lexical density of the source-language texts, but was negatively associated with formulaicity of both the source-language and the target-language texts. In addition, such techniques as digital pen recording, eye-tracking and event-related potential have been applied to understand interpreters’ cognitive load (e.g., Chen, 2020; Koshkin et al, 2018; Seeber 2011; Tiselius & Sneed, 2020). For instance, a recent eye-tracking investigation by Tiselius and Sneed (2020) into dialogue interpreting, an under-examined mode of interpreting, revealed no significant difference regarding gaze patterns between experienced and inexperienced interpreters, but indicated that interpreting into L2 in a dialogue may incur more cognitive effort than interpreting into L1.…”
Section: Interpreting Ability/competence: Construct Definitionmentioning
confidence: 99%
“…In addition, such techniques as digital pen recording, eye-tracking and event-related potential have been applied to understand interpreters’ cognitive load (e.g., Chen, 2020; Koshkin et al, 2018; Seeber 2011; Tiselius & Sneed, 2020). For instance, a recent eye-tracking investigation by Tiselius and Sneed (2020) into dialogue interpreting, an under-examined mode of interpreting, revealed no significant difference regarding gaze patterns between experienced and inexperienced interpreters, but indicated that interpreting into L2 in a dialogue may incur more cognitive effort than interpreting into L1. Similarly, in a pen-recording and eye-tracking study by Chen (2020) to examine cognitive processes during consecutive interpreting (with note-taking), it was found that L2-to-L1 interpreting appeared to be less cognitively demanding than the other direction, although a higher level of cognitive load was involved in note-taking in L2-to-L1 direction than the other way around.…”
Section: Interpreting Ability/competence: Construct Definitionmentioning
confidence: 99%
“…Keystroke logging is not particularly relevant to the study of interpreting, given that interpreters do not use a keyboard; however, a variation on this method has been employed in studies logging interpreters' use of visual support (Seeber, 2012;Stachowiak-Szymczak, 2019). Eye-tracking is a potentially productive method for use in interpreting studies, as illustrated by its use in studies involving reading back notes from consecutive interpreting (Chen, 2018) and tracking dialogue interpreters' gaze (Vranjes et al 2018;Tiselius and Sneed, submitted). Measurement of electrodermal response has been employed to investigate interpreters' responses to emotional speech during interpreting (Korpal and Jasielska, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive load is also a key topic in interpreting studies (Seeber & Kerzel, 2011), but no study has yet used the eye-tracking method to investigate cognitive load and cognitive effort in dialogue interpreting. Tiselius and Sneed (Tiselius & Sneed, 2020) report an exploratory eye-tracking study on how experienced and inexperienced interpreters may perform in a staged dialogue interpreting session (i.e., a simulated job-counseling consultation). Gaze patterns in relation to the interpreters' action (listening or speaking one or the other language) and translation direction were recorded.…”
mentioning
confidence: 99%
“…Amos and Pickering (Amos & Pickering, 2020) proposed a model of prediction-by-production in SI and Lozano-Argüelles, Sagarra and Casilla (Lozano-Argüelles, Sagarra & Casilla, 2020) investigated the impact of interpreting experience on L2 morphological anticipation. The second group includes two papers that are related to cognitive load, with Mårtensson and colleagues (Mårtensson, Eriksson, Bodammer, Lindgren, Johansson, Nyberg and Lövdén, 2020) investigating the brain basis of foreign language learning aptitude in interpreters, and Tiselius and Sneed (Tiselius & Sneed, 2020) cognitive load as reflected in gaze and eye-movements in dialogue interpreting. The third group, the remaining four papers, are related to language control and cognitive control in interpreting, with Dong and Li (Dong & Li, 2020) proposing an overall account in their attentional control model, Hervais-Adelman and Babcock (Hervais-Adelman & Babcock, 2020) focusing on the neurobiology of SI, Nour et al (Nour, Struys & Stengers, 2020) investigating the impact of interpreting experience on WM, and García et al (García, Muñoz & Kogan, 2020) reviewing the impact of SI experience on cognitive control.…”
mentioning
confidence: 99%